TATA CARA PERHITUNGAN, PENYETORAN, PELAPORAN, PENCATATAN PPN ATAS USAHA JASA KONSTRUKSI - MEIRISKA FEBRIANTI (Media Bisnis, 2016)
The purpose of this research is to analyze the calculation, payment, reporting and recording of Value Added Tax (VAT) by CV.SM in the year 2013 based on Value Added Tax (VAT) law number 42/ 2009 This research used descriptive analysis method to analyze and compare the data obtained from the company with the taxation rules. The secondary data collected are the VAT invoices 2013, monthly VAT returns, tax payment slips, annual tax return and tax collection letter. The result shows that CV. SM has done the calculation, payment and reporting Value Added Tax (VAT) in compliance with VAT regulations.